From Digital Interaction to Responsible Tourism: Unveiling the Mediating Role of Sustainable Destination Perception - Altatit Dianawati; Haris Karyadi; Diah Nofitasari; Eko Yuliawan (Jurnal Informatika Ekonomi Bisnis, 2026)
This study examines the influence of digital engagement and environmental awareness on destination sustainability perception and its impact on responsible tourism behaviour among tourists visiting Karimunjawa Island, Indonesia. The research aims to analyse both direct and indirect relationships among the variables within the context of sustainable tourism. A quantitative approach was employed, using a survey of 201 respondents who had visited Karimunjawa within the last two years. Data were collected through an online questionnaire using purposive sampling techniques and analysed using Partial Least Squares Structural Equation Modelling. The results indicate that destination sustainability perception has a significant positive effect on responsible tourism behaviour. Digital engagement significantly influences perceptions of destination sustainability and indirectly affects responsible tourism through this mediating role. However, environmental awareness does not significantly affect destination sustainability perception, either directly or indirectly through mediation effects. These findings suggest that digital interaction and online tourism communication play a more dominant role in shaping perceptions of sustainable destinations and responsible tourism behaviour than environmental awareness alone. The study contributes to the sustainable tourism literature by integrating digital engagement, environmental awareness, destination sustainability perception, and responsible tourism into a comprehensive research model. Practically, the findings provide insights for tourism stakeholders in designing digital-based sustainability communication strategies to promote responsible tourism behaviour in island tourism destinations.